Electrospun zirconia nanofibers and the acid vapor resistance. (June 2022) - Yuan, Kangkang; Jin, Xiaotong; Li, Chengshun; Wang, Xinqiang
Abstract: Excellent chemical stability against corrosive waste gases is a considerable property for ceramic fibers products applied in high temperature filtration and other harsh environment. As one of the promising ceramic fibers candidates for high temperature filtration, zirconia nanofibers (NFs) were prepared by a simple and cost-effective electrospinning technique in the present work. The thermal decomposition process, crystallization and microstructure evolution of zirconia NFs were fully analysed with Fourier-transform infrared spectroscopy (FT-IR), Thermogravimetry and differential scanning calorimetry (TG/DSC), X-ray diffraction (XRD) and Scanning electron microscope (SEM). The microstructure and grain size evolution of zirconia NFs were fully discussed. The results indicated that zirconia NFs with a diameter of about 450 nm were stable up to 1200 °C and apparent grain growth developed at above 900 °C. Furthermore, the HCl acid vapor at 150 °C was used to explore the acid resistance of zirconia NFs. It was found that zirconia NFs possessed good tetragonal phase stability while surface hydration and exfoliation on the surface happened in an acid vapor environment. The water vapor and acid vapor corrosion mechanisms were presented. Graphical Abstract: ga1 Highlights: Thermal decomposition process of zirconia precursor fibers were fully explored. The microstructure evolution of zirconia nanofibers at various temperatures were characterized. The acid vapor corrosion mechanism was presented.